Invariância de Rótulo e Shifts no Momento de Integração de um Diagrama de Feynman: termos de Superfície como Violadores da Supersimetria - Luellerson Carlos Ferreira (2019)
Implicit regularization (IR) is a method that in the momentum space allows for the calculation of Feynman diagrams in an independent manner. The idea behind the IR is to extract the ultraviolet behavior of the amplitude in the form of basic divergent integrals which depend only on the internal momenta of the diagram. All arbitrary parameters embedded in the Feynman diagram are expressed by surface terms that, within the IR, are manifested as differences between (logarithmically) divergent integrals. The surface terms are directly related to the possibility of making shifts in the integration momenta. In this work, we aim for a better understanding of how surface terms, finite but indeterminate quantities, may contaminate the physical contents of a Quantum Field Theory. Relating the freedom of labeling of Feynman diagram with the shifts operation (and the resulting appearance of surface terms), we obtained a symmetry associated with the Feynman diagrams, the Momentum Routing Invariance. We applied this invariance to the Wess- Zumino model and we could see that surface terms may violate Supersymmetry if its value is non-zero.